Superconductivity and normal state properties of non-centrosymmetric CePt3Si: a status report - Bauer, E.; Bonalde, I.; Sigrist, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
Ternary CePt3Si crystallizes in the tetragonal P4mm structure which lacks a center of inversion.Antiferromagnetic order sets in at TN≈22 . K followed by superconductivity (SC) below Tc≈ 0.75 K. Large values of H'c2≈-8.5 T/K and Hc2(0)≈5T were derived, referring to Cooper pairs formed out of heavy quasiparticles. The mass enhancement originates from Kondo interactions with a characteristictemperature TK≈ 8 K. CePt3Si follows the general features of correlated electron systems and can be arranged within the Kadowaki–Woods plot next to the unconventional SC UPt3. NMR and mSR results show that both magnetic order and SC coexist on a microscopic scale without having spatial segregation of both phenomena. The absence of an inversion symmetry gives rise to a lifting of the degeneracy of electronic bands by spin-orbit coupling. As a consequence, the SC order parameter may have uncommon features as indicated from a very unique NMR relaxation rate 1/T1 and a linear temperature dependence of the penetration depth l.